The role of international law in protecting The atmosphere (Damascus University Journal for legal sciences, 2024)
The atmosphere (atmospheric mass) is one of the largest natural resources on the planet; It is indispensable to the survival of mankind، and one of the most important sources of atmospheric pollution are human sources، where human activities are considered the largest cause of pollution in the atmosphere، to constitute a serious concern of the international community، which prompted it to conclude many international and regional treaties، and the issuance of international declarations، from For the commitment of states and facilitating capabilities in the field of cross-border protection from air pollution activities، under penalty of international responsibility that is established in the face of it in the event of any violation of the atmosphere. The question prompts us during our research، about what are the international legal rules regulating the protection of the atmosphere، and what are the existing obligations of states within the framework of international responsibility in the event of a violation of these obligations?
Keywords: Atmosphere; Pollution; International Agreements; International Responsibility